Unusual presentation of Mönckeberg’s sclerosis in the thyroid vessels of three female patients - Dastamani, Christina (Pulsus Group Inc, 2010)
Histopathological findings of Mönckeberg’s sclerosis in the thyroid vessels of three female patients are described. Two of the patients presented with papillary carcinoma and the third presented with two cystic adenomatous nodules. Lesions of chronic lymphocytic thyroiditis were observed in two of the cases. The presence of Mönckeberg’s sclerosis is an indication for further examination of patients’ vascular systems because of the high risk for cardiovascular events.